Pengaruh e-Procurement Terhadap Pencegahan Fraud Di Pemerintah Daerah Sumatera Selatan - Safitri, Rika Henda; Kalsum, Umi; Usmayanti, Vivi; Arief HS, Rosihan (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to determine the effect of implementing e-procurement on fraud prevention in Regional Government. Research has been carried out in several regional agencies in South Sumatra Province. The research was conducted using the questionnaire distribution method. The variables in this research are the e-procurement stages, namely planning, committee formation, prequalification, tender document preparation, bid evaluation, announcement, objection. The results of the research state that the implementation of e-procurement has an effect on preventing procurement fraud in the Regency/City Region of South Sumatra. Then, from the results of this research, it was also concluded that of the seven stages of e-procurement, only four stages of e-procurement had an effect on fraud prevention (document preparation stage, offer evaluation stage, announcement stage, and rebuttal stage). Meanwhile, the other three stages (planning stage, committee formation stage, and prequalification stage) in e-procurement have no effect on fraud prevention.